Anti-inflammatory Action of Curcumin and Its Use in the Treatment of Lifestyle-related Diseases. Issue 2 (2019) - Shimizu, Kana; Funamoto, Masafumi; Sunagawa, Yoichi; Shimizu, Satoshi; Katanasaka, Yasufumi; Miyazaki, Yusuke; Wada, Hiromichi; Hasegawa, Koji; Morimoto, Tatsuya
No abstract available